Ursodeoxycholic acid can be used as a steroid-tapering drug in the treatment of autoimmune hepatitis - Rukiye VARDAR,; Galip ERSÖZ,; Zeki KARASU,; Ulus S. AKARCA,; Yücel BATUR, (Turkish Journal of Gastroenterology, 2019)
-